Importance of the Brain Angiotensin System in Parkinson's Disease. (7th November 2012) - Wright, John W.; Harding, Joseph W.
Abstract : Parkinson's disease (PD) has become a major health problem affecting 1.5% of the world's population over 65 years of age. As life expectancy has increased so has the occurrence of PD. The primary direct consequence of this disease is the loss of dopaminergic (DA) neurons in the substantia nigra and striatum. As the intensity of motor dysfunction increases, the symptomatic triad of bradykinesia, tremors-at-rest, and rigidity occur. Progressive neurodegeneration may also impact non-DA neurotransmitter systems including cholinergic, noradrenergic, and serotonergic, often leading to the development of depression, sleep disturbances, dementia, and autonomic nervous system failure. L-DOPA is the most efficacious oral delivery treatment for controlling motor symptoms; however, this approach is ineffective regarding nonmotor symptoms. New treatment strategies are needed designed to provide neuroprotection and encourage neurogenesis and synaptogenesis to slow or reverse this disease process. The hepatocyte growth factor (HGF)/c-Met receptor system is a member of the growth factor family and has been shown to protect against degeneration of DA neurons in animal models. Recently, small angiotensin-based blood-brain barrier penetrant mimetics have been developed that activate this HGF/c-Met system. These compounds may offer a new and novel approach to the treatment of Parkinson's disease.